SAT0492 Treatment Effects Measured by Dynamic Contrast Enhanced MRI and Ramris for Rheumatoid Arthritis. (23rd January 2014) - Beals, C.; Baumgartner, R.; Peterfy, C.; Balanescu, A.; Mirea, G.; Harabagiu, A.; Popa, S.; Cheng, A.; Feng, D.; Fox, R.; Vallee, M.-H.; Ashton, E.; et al.
Abstract : Background: Sensitive imaging biomarkers are needed to complement clinical measures for development of drugs for rheumatoid arthritis (RA). Objectives: In this double-blind randomized methodology study, Dynamic Contrast Enhanced (DCE)-MRI and RA MRI Score (RAMRIS) were compared with conventional clinical scoring [DAS28(CRP)] after short-term treatment with infliximab or placebo. Methods: Sixty-one patients with active RA despite methotrexate treatment and with MRI-documented synovitis were randomized to infliximab 3 mg/kg IV or placebo at 4 clinical sites in Europe. MRI of the most severe hand and wrist was acquired at baseline and weeks 2, 4, and 14. Both the wrist and hand were scanned simultaneously in a single field of view using a knee coil. In addition to repeated clinical assessments with DAS28(CRP), the transfer rate of gadolinium contrast from plasma to synovium (Ktrans, primary endpoint) was measured. Two radiologists blinded to visit order also independently scored synovitis, osteitis and erosion using RAMRIS and cartilage loss using the 9-point MRI scale. 1 Results: Participants were 92% female with mean (±SD) age 50 (10) years and baseline DAS28(CRP) 6.2 (0.7). Infliximab showed greater decrease from baseline in DAS28(CRP) and DCE-MRI Ktrans in the wrist at all visits than placebo did. RAMRIS scores for synovitis and osteitis were also significantly better than placebo at each visit. RAMRIS scores for bone erosion and cartilage loss were significantly different from placebo at 14 weeks (Table ). Treatment effect sizes of infliximab therapy were similar for DAS28(CRP) (1.08), wrist Ktrans (1.00), RAMRIS synovitis (0.85) and RAMRIS osteitis (0.99). Correlation between change in DAS28(CRP) and wrist Ktrans after 14 weeks of infliximab treatment was not significant (0.10). Change in RAMRIS synovitis, however, correlated significantly with DAS28(CRP) (0.37), as did baseline wrist Ktrans (0.39) and RAMRIS synovitis (0.55), osteitis (0.21) and erosion (0.46). Conclusions: DCE-MRI and RAMRIS both showed suppression of synovitis in only 2 weeks in this multisite controlled trial with only 30 subjects per arm. RAMRIS further demonstrated suppression of osteitis in 2 weeks and suppression of erosion and cartilage loss in 14 weeks. References: Peterfy, et al. Arthritis Res Ther. 2012;14(3):R131 Liang, et al. The Indian Journal of Statistics. 2000; 62: 134-148. Disclosure of Interest: C. Beals Shareholder of: Merck Sharp & Dohme Corp., Employee of: Merck Sharp & Dohme Corp., R. Baumgartner Shareholder of: Merck Sharp & Dohme Corp., Employee of: Merck Sharp & Dohme Corp., C. Peterfy Shareholder of: Spire Sciences, LLC, Grant/research support from: Amgen, Centocor / Janssen, Pfizer / Wyeth, Abbott, Roche, Genentech, Bayer, Consultant for: Abbott, Articulinx, Merck/ Schering-Plough, Roche, UCB, Pfizer /Wyeth, AstraZeneca, Bristol Myers-Squibb, BioClinica, Celgene, Genentech, Icon Medical Imaging, Lilly, Medimmune, Moximed, Novartis, Perceptive Informatics, VirtualScopics, Jennsen, Genzyme/Sanofi, Biogen-Idec, Employee of: Spire Sciences, LLC, A. Balanescu: None Declared, G. Mirea: None Declared, A. Harabagiu: None Declared, S. Popa: None Declared, A. Cheng Shareholder of: Merck Sharp & Dohme Corp., Employee of: Merck Sharp & Dohme Corp., D. Feng Shareholder of: Merck Sharp & Dohme Corp., Employee of: Merck Sharp & Dohme Corp., R. Fox Shareholder of: Merck Sharp & Dohme Corp., Employee of: Merck Sharp & Dohme Corp., M.-H. Vallee Shareholder of: Merck Sharp & Dohme Corp., Employee of: Merck Sharp & Dohme Corp., E. Ashton: None Declared, J. DiCarlo Consultant for: Abbott, Amgen, AstraZeneca, BioClinica, Biogen-Idec, Bristol-Myers Squibb, Celgene, Centocor, Core Lab Partners, Crescendo, Eli Lilly, Genentech, Genzyme, Icon Medical Imaging, Johnson & Johnson, Merck, Novartis, Perceptive Informatics, Pfizer, Rigel, Roche, Sanofi, Samsung, UCB, Virtual Scopics, Wyeth, Employee of: Spire Sciences, LLC, B. Dardzinski Shareholder of: Merck Sharp & Dohme Corp., Employee of: Merck Sharp & Dohme Corp.